Nascent actin dynamics and the disruption of calcium dynamics by actin arrest in developing neural cell networks - Sylvester J. Gates; Phillip H. Alvarez; Kate M. O’Neill; Kan Cao; Wolfgang Losert (Communications Biology)
Abstract Waves and oscillations are key to information flow and processing in the brain. Recent work shows that, in addition to electrical activity, biomechanical signaling can also be excitable and support self-sustaining oscillations and waves. Here, we measured the biomechanical dynamics of actin polymerization in neural precursor cells (NPC) during their differentiation into populations of neurons and astrocytes. Using fluorescence-based live-cell imaging, we analyzed the dynamics of actin and calcium signals. The size and localization of actin dynamics adjusts to match functional needs throughout differentiation, enabling the initiation and elongation of processes and, ultimately, the formation of synaptic and perisynaptic structures. Throughout differentiation, actin remains dynamic in the soma, with many cells showing notable rhythmic character. Arrest of actin dynamics increases the slower time scale (likely astrocytic) calcium dynamics by 1) decreasing the duration and increasing the frequency of calcium spikes and 2) decreasing the time-delay cross-correlations in the networks. These results are consistent with the transition from an overdamped system to a spontaneously oscillating system and suggest that dynamic actin may dampen calcium signals. We conclude that mechanochemical interventions can impact calcium signaling and, thus, information flow in the brain.